Pore Preservation and Failure Mechanism of Sinian Dengying Formation Carbonate Reservoirs: A Case Study of Two Ultradeep Wells in the Sichuan Basin, Western China. (15th November 2021) - Li, Zeqi; Sun, Wei; Liu, Shugen; Li, Zhiwu; Deng, Bin; Wu, Juan; Ding, Yi; Jiao, Kun; Jin, Xin; Lu, Pengda; Tian, Tengzhen
Abstract : Despite being one of the most important factors in deep oil and gas exploration, the preservation mechanisms of ultradeep carbonate reservoirs remain poorly understood. This study performed thin-section, geochemistry, field emission scanning electron microscopy, fluid inclusion, and basin model analysis of samples from two boreholes over 8, 000 m deep in the Sichuan Basin to determine the pore features and preservation mechanism of the Sinian (Ediacaran) Dengying Formation carbonate reservoirs. The reservoir of CS well #1 is characterised by pore diameters larger than a centimetre (average porosity 7.48%; permeability 0.8562 mD), and the pores are mainly filled with dolomite or bitumen. In contrast, the reservoir of MS well #1 is predominantly composed of micron-scale residual pores (average porosity 1.74%; permeability 0.0072 mD), and the pores are typically filled with dolomite, bitumen, and multistage quartz. The burial thermal histories suggest that both reservoirs were subjected to high pressure (i.e., pressure coefficient > 1.5 ) before the Late Cretaceous. However, the pressure coefficient of the reservoir of MS well #1 has decreased to less than 1.0 owing to strong structural adjustment this well since the Late Cretaceous, which allowed other ore-forming fluids to enter and fill the pores, resulting in further compaction of the pores. In contrast, the pressure coefficient of CS well #1 is 1.1–1.2, which effectively prevented other ore-forming fluids from entering and filling the pores. The findings show that the dynamic adjustment of the Dengying Formation palaeo-gas reservoir indirectly affects the preservation or failure of the reservoir. The occurrence and geometry of bitumen in the Dengying reservoir exhibit good consistency with the pressure changes in both boreholes. In particular, bitumen with an annular shape and contraction joints in reservoir pores is widespread in CS well #1, which is attributed to the continuous preservation of palaeo-gas fields. Conversely, bitumen with a broken particle shape is located among the epigenetic minerals widespread in MS well #1, which is attributed to failure and depletion of the palaeo-gas fields.